Activation of signal transducer and activator of transcription (STAT) 1 in human chronic inflammatory bowel disease - Schreiber, S (Copyright 2002 by Gut, 2002)
Background: Increased expression of proinflammatory cytokines, including tumour necrosis factor α, interleukin 6, and interferon γ, as well as activation of proinflammatory signalling molecules such as nuclear factor kappa B, is characteristic of inflammatory bowel disease (IBD). Aims: To investigate expression and activation of signal transducer and activator of transcription (STAT) 1 in patients with IBD. Patients: Patients with active IBD (n=42), disease specificity controls (n=8), and normal controls (n=12) were investigated. Methods: Expression and activation of STAT1 were assessed by western blotting and electrophoretic mobility shift assays in extracts of endoscopic colonic biopsies. Cellular localisation was determined by immunohistochemistry. Results: Western blots and immunohistochemical staining revealed an increase in STAT1 expression and activation in mucosal samples from ulcerative colitis and to a lesser extend in Crohn's disease patients. High levels of suppressor of cytokine signalling (SOCS)-3 expression, an inhibitor of STAT activation, were observed in Crohn's disease patients and normal controls in western blot experiments whereas no differences were observed for SOCS-1 expression. Phosphorylated (p) STAT1 was mainly detected in monocytic cells and neutrophils in the inflamed mucosa. Induction of remission by systemic glucocorticoids led to a decrease in levels of pSTAT1. In vitro studies indicated a direct effect of steroid treatment on STAT1 activation. Conclusions: Expression and activation of STAT1 are predominantly heightened in ulcerative colitis and may therefore play an important role in the pathophysiology of colonic inflammation.